2019
DOI: 10.1074/jbc.ra118.006047
|View full text |Cite
|
Sign up to set email alerts
|

Trout myomaker contains 14 minisatellites and two sequence extensions but retains fusogenic function

Abstract: The formation of new myofibers in vertebrates occurs by myoblast fusion and requires fusogenic activity of the musclespecific membrane protein myomaker. Here, using in silico (BLAST) genome analyses, we show that the myomaker gene from trout includes 14 minisatellites, indicating that it has an unusual structure compared with those of other animal species. We found that the trout myomaker gene encodes a 434 -amino acid (aa) protein, in accordance with its apparent molecular mass (ϳ40 kDa) observed by immunoblo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 37 publications
7
27
0
Order By: Relevance
“…in fry, juvenile and to a lesser extend in mature fish. Our results clearly indicate that the expression pattern of myomixer is similar to that of the myomaker in trout (Landemaine et al, 2019) during embryonic and post-larval stages. In addition, we did not observe myomixer and myomaker expression in myofibers, but only in small cells that should be fusing muscle precursors.…”
Section: Discussionsupporting
confidence: 66%
See 4 more Smart Citations
“…in fry, juvenile and to a lesser extend in mature fish. Our results clearly indicate that the expression pattern of myomixer is similar to that of the myomaker in trout (Landemaine et al, 2019) during embryonic and post-larval stages. In addition, we did not observe myomixer and myomaker expression in myofibers, but only in small cells that should be fusing muscle precursors.…”
Section: Discussionsupporting
confidence: 66%
“…To determine whether myomixer is up-regulated during the muscle regeneration, we measured its expression in muscle following mechanical injury. In our previous study, we observed that the formation of new fibers and the increase of myogenin expression occurred 30 days following injury (Landemaine et al, 2019). Consistently, myomixer expression remained stable up to 16 days and was sharply up-regulated on day 30 with 6-fold higher expression in injured muscle than in the control one ( Figure 5).…”
Section: Myomixer Is Up-regulated During Muscle Regeneration and Myotsupporting
confidence: 69%
See 3 more Smart Citations